Dialogism in Corporate Social Responsibility Communications: Conceptualising Verbal Interaction Between Organisations and Their Audiences - Brennan, Niamh M. (Journal of business ethics, 2013)
We conceptualise CSR communication as a process of reciprocal influence between organisations and their audiences. We use an illustrative case study in the form of a conflict between firms and a powerful stakeholder which is played out in a series of 20 press releases over a 2-month period to develop a framework of analysis based on insights from linguistics. It focuses on three aspects of dialogism, namely (i) turn-taking (co-operating in a conversation by responding to the other party), (ii) inter-party moves (the nature and type of interaction characterising a turn, i.e. denial, apology or excuse) and (iii) intertextuality (the intensity and quality of verbal interaction between the parties). We address the question: What is the nature and type of verbal interactions between the parties? First we examine (a) whether the parties verbally interact and then (b) whether the parties listen to each other. We find evidence of dialogism suggesting that CSR communication is an interactive process which has to be understood as a function of the power relations between a firm and a specific stakeholder. Also, we find evidence of intertextuality in press releases by six firms which engage in verbal interaction with the stakeholder. We interpret this as linguistic evidence of isomorphic processes relating to CSR practices resulting from the pressure exerted by a powerful stakeholder. The lack of response by ten firms that fail to issue press releases suggests a strategy of ‘watch-and-wait’ with respect to the outcome of the conflict.